Incidental Finding of Panhypogammaglobulinaemia in Pregnancy-an Extremely Rare Condition (Global Journal of Medical Research, 2014)
A 22 year old lady, G2P0 presented at a 311 weeks of gestation with an abnormal group and antibody test found incidentally during routine 28 week blood testing. She reported no past medical history apart from medication controlled gestational diabetes and denied any family history of autoimmune diseases. She was subsequently diagnosed with panhypogam-maglobulinemia. After consultation with an immune-ologist, a number of blood investigations were undertaken, all of which were negative, except for an MRI which showed a possible small thymoma. All fetal ultrasounds were unremarkable. Given the importance of transplacental immunoglobulin (Ig) transfer in the third trimester and the concern of serious infection during pregnancy she has was commenced on intravenous immunoglobulin (IVIg). After a loading dose of IVIg (0.6mg/kg) and a subsequent dose (0.4mg/kg) her Ig level was 10. She was administered a third dose and it was decided that her Ig levels be monitored weekly and IVIg only administered should her levels drop below 7. Since her Ig levels dropped to 6.9g/L at 37 5 weeks of gestation, she received another dose (0.4mg/kg). She underwent a normal delivery at 391 weeks and was diagnosed with a thymoma postnatally.